Mobile Grid SEAS: Simple Energy-Aware Scheduler - Rodríguez, Juan Manuel (2010)
In the last few years, several millions of high-capable mobile devices were sold around the globe. Therefore, integrating mobile devices to Grid systems may increase significantly their resources. However, mobile devices have more limited resources than personal computers or servers. In particular, minimizing energy consumption is very important because mobile devices rely on battery as energy supply. We propose a novel job scheduler that aims to use the energy in an efficient way. To implement it, we developed a simple but effective battery estimation model. In some experiments our energy aware scheduler outperformed traditional Grid schedulers to effectively address energy constrains in mobile Grids.